Five year experience in management of perforated peptic ulcer and validation of common mortality risk prediction models – Are existing models sufficient? A retrospective cohort study. (February 2015) - Anbalakan, K.; Chua, D.; Pandya, G.J.; Shelat, V.G.
Abstract: Background: Emergency surgery for perforated peptic ulcer (PPU) is associated with significant morbidity and mortality. Accurate and early risk stratification is important. The primary aim of this study is to validate the various existing MRPMs and secondary aim is to audit our experience of managing PPU. Methods: 332 patients who underwent emergency surgery for PPU at a single intuition from January 2008 to December 2012 were studied. Clinical and operative details were collected. Four MRPMs: American Society of Anesthesiology (ASA) score, Boey's score, Mannheim peritonitis index (MPI) and Peptic ulcer perforation (PULP) score were validated. Results: Median age was 54.7 years (range 17–109 years) with male predominance (82.5%). 61.7% presented within 24 h of onset of abdominal pain. Median length of stay was 7 days (range 2–137 days). Intra-abdominal collection, leakage, re-operation and 30-day mortality rates were 8.1%, 2.1%, 1.2% and 7.2% respectively. All the four MRPMs predicted intra-abdominal collection and mortality; however, only MPI predicted leak (p = 0.01) and re-operation (p = 0.02) rates. The area under curve for predicting mortality was 75%, 72%, 77.2% and 75% for ASA score, Boey's score, MPI and PULP score respectively. Discussion and conclusion: Emergency surgery for PPU has low morbidity and mortality in our experience. MPI is the only scoring system which predicts all – intra-abdominal collection, leak, reoperation and mortality. All four MRPMs had a similar and fair accuracy to predict mortality, however due to geographic and demographic diversity and inherent weaknesses of exiting MRPMs, quest for development of an ideal model should continue. Highlights: Early presentation, prompt diagnosis and emergent surgery are the pillars to successful management and good outcomes of PPU. To provide optimal care, it is important to stratify patients into high and low risk of mortality, ideally prior to surgery. All the four MRPMs tested had a similar moderate accuracy for mortality prediction in our experience. There is a potential for improvement of existing MRPMs; especially due to geographic and demographic diversity. MPI is the only scoring system which predicts all – intra-abdominal collection, leak, re-operation and mortality.